To export, or not to export: how nuclear export factor variants resolve Piwi's dilemma. - Wang, S.; Lu, X.; Qiu, D.; Yu, Y. (Biochemical Society Transactions, 2021)
Piwi-interacting RNAs (piRNAs) defend animal gonads by guiding PIWI-clade Argonaute proteins to silence transposons. The nuclear Piwi/piRNA complexes confer transcriptional repression of transposons, which is accompanied with heterochromatin formation at target loci. On the other hand, piRNA clusters, genomic loci that transcribe piRNA precursors composed of transposon fragments, are often recognized by piRNAs to define their heterochromatic identity. Therefore, Piwi/piRNA complexes must resolve this conundrum of silencing transposons while allowing the expression of piRNA precursors, at least in Drosophila germlines. This review is focused on recent advances how the piRNA pathway deals with this genetic conflict.